Implementing traffic conditioner using token bucket and leaky bucket / Chia Kai Yan - Chia , Kai Yan (2004)

(untitled)
Since network is expanding from time to time, therefore network simulator is required as a tool investigate performance of the network effectively. Without building a real network the performance of the network can be analyzed. UMJaNetSim is a network simulator that provides graphical user interface for user to allocate the components and set the respective parameters virtually and get a prediction result. UMJaNetSim is running in ATM environment recently. Based on the result of research, the performance of network simulator will be increse if UMJaNetSim run in Differsv environment. In order to develop UMJaNetSim in a Diffserv environment, Traffic conditioner is required. This project fouceses on the development for Traffic Conditioning using Token Bucket and Leaky Bucket. By implementing a Traffic Conditioner in UMJaNetSim, a more effective traffic flow handling system which consists of metering, marking, shaping and dropping stages will be produced. Besides that, Traffic Conditioner will avoid the traffic flow from any traffic congestion. Furthermore, the simulator is capable of multithtrad operation and platform independent. Thus, the developed simulator can run on different platforms like Windows or UNIX.